Photoactivated release of membrane impermeant sulfonates inside cells. Issue 32 (23rd March 2021) - Caldwell, Stuart T.; O'Byrne, Sean N.; Wilson, Calum; Cvetko, Filip; Murphy, Michael P.; McCarron, John G.; Hartley, Richard C.
Abstract : Photocaged sulfonate delivers membrane impermeant compounds to cells. Abstract : Photouncaging delivers compounds with high spatial and temporal control to induce or inhibit biological processes but the released compounds may diffuse out. We here demonstrate that sulfonate anions can be photocaged so that a membrane impermeable compound can enter cells, be uncaged by photoirradiation and trapped within the cell.